Evolution of structural and magnetic properties of nickel oxide nanoparticles: Influence of annealing ambient and temperature - Jafari, Atefeh; Pilban Jahromi, Siamak; Boustani, Komail; Goh, Boon Tong; Huang, Nay Ming (Elsevier, 2019)
Nickel oxide (NiO) nanoparticles (NPs) are synthesized using the sol-gel method. The effect of annealing atmosphere type, including air, O2 and annealing temperature (TA) on the structural, morphological and magnetic properties of NiO NPs was investigated using X-ray diffraction (XRD), transmission electron microscopy (TEM), and vibrating sample magnetometer (VSM) analysis. For this purpose, NiO NPs are annealed at 400, 500, 600, 700 and 800 °C. The magnetic properties of the NPs change as a result of increasing crystallite size in terms of TA in both atmospheres. These variations are different according to the type of the annealing atmosphere. At lower temperatures (TA < 600 °C), the NPs that annealed in the O2 atmosphere have higher crystallinity, larger lattice constant, and lower magnetization and coercivity. At higher temperatures, the structural and magnetic properties of the samples in both atmospheres are more similar.